Comparison of the efficacy and safety of different growth factors in the treatment of diabetic foot ulcers: an updated network meta-analysis - Tian, Jianzhou; Yao, Guanghui; Tian, Tian; Li, Xinlin; Li, Shaoru; Wu, Chengda; Zhang, Saisheng (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to evaluate the efficacy and safety of different growth factors (GFs) in the treatment of diabetic foot ulcers (DFUs) through a network meta-analysis.MethodsA systematic search was conducted in PubMed, Embase, The Cochrane Library, and Web of Science to identify randomized controlled trials (RCTs) comparing GFs with standard of care (SOC) or comparing different GFs for the treatment of DFU. Two independent reviewers screened the studies, extracted data, and assessed the quality of the included literature according to predefined inclusion and exclusion criteria. A network meta-analysis was performed using R software. Relative risk (RR) was used as the effect measure for dichotomous outcomes, and mean difference (MD) was used for continuous outcomes.ResultsA total of 51 RCTs, involving 3,401 patients with DFUs and six different types of GFs, were included. The network meta-analysis revealed that, compared with SOC, epidermal growth factor (EGF), platelet-derived growth factor (PDGF), and platelet-rich plasma (PRP) significantly improved the healing rate. EGF and PRP also significantly reduced healing time, while PDGF significantly reduced ulcer area. Moreover, PRP was associated with a significant reduction in the incidence of adverse events (AEs) and amputation rates. In terms of ranking: For healing rate, the top three GFs were EGF, vascular endothelial growth factor (VEGF), and granulocyte colony-stimulating factor (G-CSF). For healing time, EGF, PRP, and fibroblast growth factor (FGF) ranked the highest. For ulcer area reduction, PDGF, EGF, and PRP were the top-ranking interventions. Regarding AEs, PRP, PDGF, and FGF showed the most favorable safety profiles. For amputation rate, PRP, G-CSF, and PDGF were ranked the highest.ConclusionAlmost all GFs outperformed SOC in terms of healing rate, healing time, and ulcer area reduction. Compared to SOC, EGF, PDGF, and PRP significantly improved healing rates; EGF and PRP significantly reduced healing time; and PDGF significantly decreased ulcer area. Among them, EGF may be the most effective GF. Except for VEGF, which significantly increased AEs, other GFs did not show a significant increase in AEs compared to SOC. PRP had the lowest amputation rate and incidence of AEs.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251035765